The Effectiveness of Group Guidance Using the Pass The Compliment Game Technique to Enhance Students' Self-Confidence - Hasibuan, Seri Jumiarti; Siregar, Alfin (Devotion : Journal of Research and Community Service, 2023)
This study aims to determine the effectiveness of group guidance with the pass the compliment game technique to increase students' confidence in SMP Muhammadiyah Sukaramai in the 2023/2024 academic year. The method used in this research is a quantitative approach with a quasi-experimental research method, which is an experimental research method that allows researchers to control as many variables as possible from the existing situation. The results showed that no that there is no increase in student confidence by carrying out Group Guidance services through the 'pass the compliment' game technique for grade VIII of SMP Muhammadiyah Sukaramai, Tegal Sari I, Kec. Medan Area, North Sumatra 20216 for the 2023/2024 academic year.